Evaluation of Financial Technology's Performance in Islamic Banking across Indonesia, Malaysia, and Brunei Darussalam - Rahmi, Asri Noer; Palupi, Ade; Siska Pratiwi, Silvia; Annisa Buys, Witrie (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This research aims to analyze the effect of financial technology on financial performance in Islamic banking Indonesia, Malaysia and Brunei. The measurement method used in this research the percentage of income derived from the financial technology in the financial statements presented in Islamic banking registered with the Financial Services Authority (OJK). The data used is secondary data obtained from the annual financial statements. population in this research Islamic banking in Indonesia period 2016-2020. The sampling method in this research using purposive sampling method. The number of samples obtained is 129 samples. The data analysis used is the classical assumption test and multiple linear regression analysis. The method analysis data using SPSS version 25. The results of the analysis that has been carried out in this research, it shows that FDR, DER, BOPO, Inflation and Islamic Banking have a significant effect on financial technology in Islamic banking. Meanwhile, financial performance represented by ROA has a significant negative effect on financial technology. Where the increasing income generated by Islamic banking does not necessarily mean that the bank will improve the quality of its financial technology. All variable contribution to the development of financial technology in Islamic banking in Indonesia, Malaysia and Brunei. This shows that the realization that had carried out describes the situation and the condition of the financial performance of Islamic banking on the financial technology.